Reviews in Modern Astronomy 2006
DOI: 10.1002/9783527619030.ch2
|View full text |Cite
|
Sign up to set email alerts
|

High‐Velocity Clouds and the Local Intergalactic Medium

Abstract: In this article I review recent observations of the gaseous halos of galaxies and the intergalactic medium at low redshift. In the first part I discuss distribution, metal content, and physical properties of the Galactic intermediate- and high-velocity clouds and the hot halo of the Milky Way. Recent absorption and emission measurements show that the Galaxy's tidal interaction with the Magellanic Clouds, the infall of low-metallicity gas, as well as the circulation of gas as part of the galactic fountain contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…Although the gas density n h of the halo, before the injection of the HVCs, was probably low, n h was not zero. The local intergalactic medium has low volume densities, 10 −6 −10 −4 cm −3 (Richter 2006). If n h ≈ 10 −6 atoms cm −3…”
Section: Results Of the Dynamical Modelmentioning
confidence: 99%
“…Although the gas density n h of the halo, before the injection of the HVCs, was probably low, n h was not zero. The local intergalactic medium has low volume densities, 10 −6 −10 −4 cm −3 (Richter 2006). If n h ≈ 10 −6 atoms cm −3…”
Section: Results Of the Dynamical Modelmentioning
confidence: 99%
“…Observations of the Milky Way and other nearby galaxies carried out in the 21 cm line have shown that spiral galaxies commonly also exhibit extraplanar H i structures that indicate inflows, outflows, and merger processes in these systems (see reviews by Wakker & van Woerden 1997;Richter 2006;Putman et al 2012). In the Milky Way, such extraplanar neutral gas structures manifest themselves as the so-called high-velocity clouds (HVCs), which have column densities within the range NHI ∼ 10 18 − 10 20 cm −2 .…”
Section: H I Gas Componentmentioning
confidence: 99%
“…During the last two decades, significant progress was achieved in our understanding of the distribution and physical properties of circumgalactic and intergalactic gas in the Local Group (hereafter LG; e.g., Wakker & van Woerden 1997;Richter 2006;Putman et al ⋆ snuza@aip.de 2012, for reviews on this topic). Recent observational campaigns including 21 cm radio observations of neutral hydrogen (e.g., Thilker et al 2004;Kalberla & Haud 2006;Kerp et al 2011), and absorption-line measurements of neutral and ionized gas in the optical and ultraviolet (UV; e.g., Sembach et al 2003;Collins et al 2005Collins et al , 2009Ben Bekhti et al 2008Richter et al 2009Richter et al , 2012]; Herenz et al 2013;Rao et al 2013) indicate the extreme multi-phase character of circumgalactic gas within the virial radii of the Milky Way and Andromeda galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…HVCs also have been brought into relation with primordial building blocks of galaxies in a hierarchical formation scenario (e.g., Oort 1966;Blitz et al 1999). A powerful method of analysing the characteristics of IVC and HVC gas at low redshifts is to analyse high-resolution ultraviolet (UV) and optical absorption spectra together with H i 21-cm emission data (Richter 2006;Ben Bekhti et al 2008). The combination of these data provides important information about the spatial distribution and the physical properties of the clouds.…”
Section: Introductionmentioning
confidence: 99%